1289 Gender Representation in The Authorship of Surgical Journals. (12th October 2021) - Arshad, S; Gallivan, E; Skinner, H; Burke, J; Young, A
Abstract: Introduction: Despite the increase in female doctors graduating from medical schools internationally, gender disparity in surgery remains. This disparity is also evident in academic surgery. This study aims to quantify the extent of gender disparity in the authorship of articles in major surgical journals. Method: The Top 10 Surgical Journals were identified using SCImago Journal Rank indicator. Authorship details for papers published in 2019 were collected. Authors were assigned as female, male or unknown using Gender API software (Gender API, Germany). For each journal, the percentage of first author, last author, corresponding author and all authors split by gender was interrogated. Gender differences by publication type were also identified. Results: 9 of the 10 journals had full names publicly available. Overall, 2414 manuscripts were interrogated which included 16, 277 number of authors. Respectively, females and males accounted for 29.8% [22.9-34.9%] (N = 655) and 62.4% [56.3-70.2%] (N = 1419) of first authors, 20.6% [11.8-27.1%] (N = 453) and 74.2% [65.6-84.1%] (N = 1706) of last authors, 23.9% [14.9-29.6%] (N = 510) and 69.9% [60.5-79.3%] (N = 2341) of corresponding authors and in total 27% [19.4-31.6%] (N = 4298) and 65.5% [58.6-73.4%] (N = 9982) of all authors. The wide range in these results could be a result of various factors. Conclusions: This study has identified a gender imbalance in authorship positions, with the greatest difference observed in the most senior author position. Whether this is reflective of the current disparity observed in senior academic surgery positions or due to gender discrimination is unclear.